Volume 7: 31st International Conference on Design Theory and Methodology 2019
DOI: 10.1115/detc2019-97400
|View full text |Cite
|
Sign up to set email alerts
|

Design Innovation With Additive Manufacturing: A Methodology

Abstract: Additive manufacturing (AM) has matured rapidly in the past decade and has made significant progress towards a reliable and repeatable manufacturing process. The technology opens the doors for new types of innovation in engineering product development. However, there exists a need for a design process framework to efficiently and effectively explore these newly enabled design spaces. Significant work has been done to understand how to make existing products and components additively manufacturable, yet there s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Table 1 lists these 18 characteristics and provides references to the supporting literature. Although much additional research in this area has been published since the survey was conducted in 2019 (e.g., Perez et al 2019;Prabhu et al 2019;Schumacher et al 2019;Valjak & Bojčetić 2019;Watschke et al 2019;Wiberg, Persson, & Ölvander 2019;Dordlofva & Törlind 2020;Prabhu et al 2020b;Valjak et al 2020), it was conciously decided not to update Table 1, because of the results' direct connection to the development of the questionnaire used to evaluate the method (see Sections 3-3.3).…”
Section: /29mentioning
confidence: 99%
“…Table 1 lists these 18 characteristics and provides references to the supporting literature. Although much additional research in this area has been published since the survey was conducted in 2019 (e.g., Perez et al 2019;Prabhu et al 2019;Schumacher et al 2019;Valjak & Bojčetić 2019;Watschke et al 2019;Wiberg, Persson, & Ölvander 2019;Dordlofva & Törlind 2020;Prabhu et al 2020b;Valjak et al 2020), it was conciously decided not to update Table 1, because of the results' direct connection to the development of the questionnaire used to evaluate the method (see Sections 3-3.3).…”
Section: /29mentioning
confidence: 99%
“…Here the AM design knowledge is written with formal syntax and further described with schematics and examples. The DP are organised in four categories (product, business process, design process, printing) and are to be used in Design Innovation with AM Methodology (Perez, Lauff, et al, 2019). With this transformation, their applicability is expended to be used throughout the design process, but also can be used in the business assessment of AM product development.…”
Section: Figure 1 Flow Diagram Of Conducted Systematic Literature Reviewmentioning
confidence: 99%
“…Blake Perez et al (2019), who investigated how AMT can be used from the outset of the design process, found that AMTs are not simply tools for product and parts production. AMTs are powerful tools that are useful at all levels of abstraction and in phases of the design process.…”
Section: Jmtm 321mentioning
confidence: 99%